Changes in Chemical Composition, Sources, and Health Risk of PM2.5 with Sand Storm at a Small City in North China - Jihong Wei; Ting Hou; Zhiyong Li; Songtao Guo; Zhenxin Li (Aerosol and Air Quality Research)
Abstract Sand storm (SS) is highly concerned based on its adverse impacts on environment and health. A field observation was conducted in Dingxing County within the Beijing-Tianjin-Hebei region from 16 March to 9 April 2021 covering two SS episodes to evaluate the SS impacts on PM2.5 components, health risks, and sources. From the non-SS period (NSSP) to the SS period (SSP), more increase was found in PM10 (114–300 µg m−3) than PM2.5 (61.5–75.2 µg m−3), suggesting the obvious increment of coarse particles (PM2.5–10) in the SSP. PM2.5 reconstruction indicated that higher dust of 54.0 µg m−3 and trace element oxides (TEO) of 0.234 µg m−3 were found in the SSP, evidencing their immigration from the sand dust. In consequence, the elevated exposure risks via inhalation including carcinogenic and non-carcinogenic were found in the SSP. More attention should be paid to high non-carcinogenic risks of 2.49 for adults and children in the SSP. Again, the concentrations of organic carbon (OC) and secondary organic carbon (SOC) increased in the SSP, especially in the case of SOC. High usage of coal and biomass for heating purpose in Mongolia and Inner Mongolia might be an explanation. However, the mass contributions of nine water-soluble ions to PM2.5 decreased from 54.0% to 33.5% due to their low contents in sand dust. Seven sources including construction dust (CD), biomass burning (BB), secondary inorganic aerosols (SIA), industrial emissions (IN), vehicle emissions (VE), coal combustion (CC), and soil dust (SD) were recognized by positive matrix factorization (PMF) model. SD was the biggest contributor in the SSP and accounted for 68.8% of the PM2.5 mass. VE contributed highest to PM2.5 in NSSP, indicating the effective emission control on industries and coal combustion.